A Comparative Study Between Some Physical and Functional Abilities - Hashwsh, Fatima; Gamila, Israa (Journal of Physical Education, 2009)
The Importance of the Research relays on the level of some physical and functional abilities of female individual and team sports a matter that led coaches to select few female athletes to perform in many sports. This fact led these few female athletes to have a high level of physical and functional abilities compared to other female athletes. The Researchers used the deceptive Research. The subject were (87) elite female athletes of team sports (Basketball, Handball and Volleyball) and Individual sports (Gymnastics, athletics and tennis) of the season (2008). Many physical and Functional tests have been conducted to evaluate physical and Functional abilities. The data was treated using proper statistical operation like mean, Standard Deviation etc and through the results the Researchers Concluded the following; 1. There is a Variance in the level of physical fitness among female players in favor of Basketball and Handball players of team sports and athletics players of individual sports. 2. There is a variance in the level of functional abilities among the players in favor of Basketball and Handball players followed by gymnastics and athletics players. 3. There are no significant differences in pulse variable for the subjects of the study. The Researchers Recommended making other Studies and Researches about Women's sports to uplift the level of Women's sport in Iraq.